2017
DOI: 10.1080/10715762.2017.1388504
|View full text |Cite
|
Sign up to set email alerts
|

Decreased reproductive performance in xCT-knockout male mice

Abstract: Sulphoxidation occurs in protamines that are enriched in cysteine and supplies chromatin for packaging. The extracellular fluid contains higher levels of oxidised cysteine (cystine), and some cells utilise system x, a cystine transporter in which xCT is the main protein component, to fulfil the need for cysteine. We hypothesised that system x might ensure the supply of cysteine needed for spermatogenesis. The reproductive ability of xCT male mice at 6- to 18-weeks of age appeared to be lower than xCT male mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…It is interesting that spermatozoa is one of the few cells constitutively expressing the SLC7A11 along with thymus, spleen and brain (33); mRNA is present in testis and the SLC7A11 knock out mouse display subfertility (67). The SLC7A11 is upregulated in many cancer cell lines (14,80), interestingly, and as seems to occur as well in the spermatozoa, high expression of the SLC7A11 in cells, is linked to high activity of the PPP (90), with cells expressing high amounts of this protein expressing also high amounts of enzymes involved in the PPP, particularly G6PD.…”
Section: Metabolic Disfunction Production Of Ros In the Spermatozoamentioning
confidence: 99%
“…It is interesting that spermatozoa is one of the few cells constitutively expressing the SLC7A11 along with thymus, spleen and brain (33); mRNA is present in testis and the SLC7A11 knock out mouse display subfertility (67). The SLC7A11 is upregulated in many cancer cell lines (14,80), interestingly, and as seems to occur as well in the spermatozoa, high expression of the SLC7A11 in cells, is linked to high activity of the PPP (90), with cells expressing high amounts of this protein expressing also high amounts of enzymes involved in the PPP, particularly G6PD.…”
Section: Metabolic Disfunction Production Of Ros In the Spermatozoamentioning
confidence: 99%
“…The availability of cysteine/cystine is the rate-limiting step in GSH synthesis, with cysteine incorporated via the Na+-dependent Alanine-Serine-Cysteine (ASC) group or transporters such as ACS1 (SLC7A10) [17][18][19][20] and cystine incorporated via the soluble family 7 carrier member 11 (SLC7A11) antiporter, the Na+-independent exchange system for cystine/glutamate [18]. SLC7A11 is constitutively expressed in a limited number of organs, such as the thymus, spleen and brain [21], but SLC7A11 mRNA is expressed in testis and SLC7A11 knockout male mice display reduced reproductive performance [22]. Moreover, cysteine is also synthetized from methionine by the enzymes cystathionine beta-synthase (CBS) and cystathionase.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that cys- tine addition to casein-based low protein diet increases plasma cystine about two-fold (18). In a low protein diet, testicular cystine may be reduced from normal amount (19), which would be necessary to produce cysteine-rich protein, protamine that packages chromatin into sperm head (20). Under the normal lighting condition, cystine addition to low protein diet did not increase plasma testosterone (9PC) nor the rhythm.…”
Section: Resultsmentioning
confidence: 99%